Khaled Hosseini's A Thousand Splendid Suns as a Child-Rescue and Neo-Orientalist Narrative - Golubeva, Olga; Al-Dagamseh, Abdullah M (CLCWeb : Comparative literature and culture, 2017)
In their article "Khaled Hosseini's A Thousand Splendid Suns as a Child-Rescue and Neo-Orientalist Narrative" Abdullah Mohammad Dagamseh and Olga Golubeva argue that the novel contributes to hegemonic Eurocentric discourse by showing the superiority and benevolence of the West. In contrast to existing scholarly focus on Hosseini's portrayal of female characters, this article highlights how children of both sexes are represented. The authors' aim is to show how Hosseini's picture of children affected by war contributes to the neo-Orientalist and child-rescue discourses, justifying the foreign involvement in Afghanistan's internal affairs. Moreover, Dagamseh and Golubeva argue that the use of universal values and the seemingly noble cause of bettering the lives of children in Afghanistan contribute to the stereotypical discourse of a "progressive" West and an "underdeveloped" East.